Building Scientific Capability and Reducing Biological Threats: The Effect of Three Cooperative Bio-Research Programs in Kazakhstan - Yeh, Kenneth B.; Tabynov, Kairat; Parekh, Falgunee K.; Maltseva, Elina; Skiba, Yuriy; Shapiyeva, Zhanna; Sansyzbai, Ablay; Frey, Stefan; Essbauer, Sandra; Hewson, Roger; Richards, Allen L.; Hay, John (Frontiers in Public Health, 2021)
Cooperative research programs aimed at reducing biological threats have increased scientific capabilities and capacities in Kazakhstan. The German Federal Foreign Office’s German Biosecurity Programme, the United Kingdom’s International Biological Security Programme and the United States Defense Threat Reduction Agency’s Biological Threat Reduction Program provide funding for partner countries, like Kazakhstan. The mutual goals of the programs are to reduce biological threats and enhance global health security. Our investigation examined these cooperative research programs, summarizing major impacts they have made, as well as common successes and challenges. By mapping various projects across the three programs, research networks are highlighted which demonstrate best communication practices to share results and reinforce conclusions. Our team performed a survey to collect results from Kazakhstani partner scientists on their experiences that help gain insights into enhancing day-to-day approaches to conducting cooperative scientific research. This analysis will serve as a basis for a capability maturity model as used in industry, and in addition builds synergy for future collaborations that will be essential for quality and sustainment.